Challenges in the Risk Management System for Developing a Successful Business Environment - Jermsittiparsert, Kittisak; Thanh Nguyen, Phong; Thuy To Nguyen, Quyen Le Hoang; Bich Huynh, Vy Dang; Shankar, K. (Opción, 2019)
The managing the risk is becoming a key practice in most of the organiza- tion. The problems that are consistently arises concern this approach. To develop competitive advantage in their respective business and to handle the issues in a better way every company is developed the policies of risk management. Every business is all about taking the risk. For an organization risk poor management can cause the adverse losses. Minimizing the risk and set the risk on to a level that can accept is the main objective on any risk management policy or program.